2015
DOI: 10.1007/s00381-015-2973-2
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol via estrogen receptor beta inhibits chondrogenesis of mouse vertebral growth plate in vitro

Abstract: Estradiol via estrogen/estrogen receptor β axis inhibits the proliferation and differentiation of VGP chondrocytes, which might give some new insight into the regulatory mechanism of bone development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Further, we showed that Sox9 down-regulation is critical to cause GP retirement or closure. The factors that down-regulate SOX9 at puberty likely include estrogen signaling, as this pathway is well known to cause pubertal growth arrest and was also shown to control Sox9 expression in chondrocytes in vitro (52)(53)(54)(55). Our findings should thus motivate further research to fully decode the mechanisms driving GP maintenance and closure.…”
Section: Discussionmentioning
confidence: 75%
“…Further, we showed that Sox9 down-regulation is critical to cause GP retirement or closure. The factors that down-regulate SOX9 at puberty likely include estrogen signaling, as this pathway is well known to cause pubertal growth arrest and was also shown to control Sox9 expression in chondrocytes in vitro (52)(53)(54)(55). Our findings should thus motivate further research to fully decode the mechanisms driving GP maintenance and closure.…”
Section: Discussionmentioning
confidence: 75%
“…13, cells or explants were serum-starved overnight prior to stimulation. Chondrocyte cultures were supplemented with physiological concentrations estrogen (synthetic; 0.1nM; Sigma-Aldrich, shanghai, China), and with or without estrogen receptor inhibitors-ERαinhibitor MPP 25 (20uM; Sigma-Aldrich, shanghai, China) and ERβ inhibitor PHTPP 26,27 (20uM; Sigma-Aldrich, shanghai, China). Later, recombinant human TGF-β1 (10 ng/mL; Peprotech, shanghai, China) and IL-1β (1 ng/mL; Peprotech, shanghai, China) were added into the culture medium, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed regulation of skeletal growth by ERβ in female (Lindberg et al 2001) but not in male mice (Vidal et al 2000). Furthermore, a recent in vitro study suggested an inhibitory effect of ERβ on chondrocyte proliferation (Zeng et al 2016). Taking all this into account, it is still possible that ERβ activation may have an effect on bone growth.…”
Section: :3mentioning
confidence: 99%